2020
DOI: 10.1007/s40962-020-00532-0
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Cryogenic Treatment (SCT) Effects on the Mechanical Properties of High Cr Cast Iron: Low-Carbon Cast Steel Bimetallic Casting

Abstract: The shallow cryogenic (subzero) treatment (SCT) effect on the mechanical properties of the bimetallic casting used in the crushing industry has been investigated. Examination methods include sand casting, heat treatment and SCT, Charpy impact test, optical microscope, scanning electron microscope, microanalysis of the chemical composition (energy dispersive spectroscopy-EDS), x-ray diffraction, and hardness measurement. Two bimetallic castings (single casting containing two layers, one of low-carbon cast steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…From the XRD diffraction pattern, RA can be observed in Q in small amounts, but not in other samples. Moreover, Figure 1b reveals that {211} α [ 46 ] diffraction peak in all specimens deviates to the left, indicating lattice expansion. There is a slight movement of {211} α peaks in Q–T and D 5h –T, while {211} α diffraction peaks in Q and D 5h shift to the left severely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the XRD diffraction pattern, RA can be observed in Q in small amounts, but not in other samples. Moreover, Figure 1b reveals that {211} α [ 46 ] diffraction peak in all specimens deviates to the left, indicating lattice expansion. There is a slight movement of {211} α peaks in Q–T and D 5h –T, while {211} α diffraction peaks in Q and D 5h shift to the left severely.…”
Section: Resultsmentioning
confidence: 99%
“…about DCT focused on PM HSS, [30,46] and few mentioned cast HSS. [22,45] Nevertheless, there are notable differences between cast HSS and PM HSS in terms of their grain size and carbide distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the result, after these operations it is possible to obtain material of the desired microstructure with specific physical and mechanical properties (Hamid, 2020;Ahaneku et al, 2012). Several scientists (Özdemir, 2021;Ahaneku et al, 2012;Nair et al, 2017;Wang et al, 2018) have identified specific features of thermally hardened steel samples, such as higher Brinell hardness, higher values of yield point and tensile strength and reduced relative elongation. Since the hardening of steel proceeds during short period of time, most of the temperature transformations occur in the outer layer of the steel bar (in the so-called "shell").…”
Section: Literature Reviewmentioning
confidence: 99%
“…The wear, hardness, strength, toughness, and electrical properties of electrodes are enhanced by cryogenic treatment, which also enhances dimensional accuracy [ 29 , 30 ]. Ozdemir [ 31 ] found that a shallow CT at −84 °C increased the toughness, hardness, and wear of Cr-Fe compared to low-carbon cast steel. Senthilkumar and Rajendran [ 32 ] found that shallow cold working improved En 19 steel’s wear properties by 114% and deep cold working by 214%.…”
Section: Introductionmentioning
confidence: 99%